PENGARUH PERBEDAAN HST (HARI SETELAH TANAM) TERHADAP DAYA KECAMBAH JAGUNG DAN SORGUM - Annisa Hakim; Fazryah, Nur Rachmy; Maulidina, Faradisa Syafrin; Salsabila, Shafa; Rayani, Tera Fit; Lestari, Firtriani Eka Puji (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2024)
The aim of this research was to examine the germination test of corn seeds and sorghum seeds based on differences in harvest age (HST). This research was carried out in the Laboratorium basah of Technology and Livestock Management at the IPB Vocational School, Sukabumi Campus in November 2023. The method used in this research was seed germination using an opaque paper substrate with a rolled paper test set in plastic and then stored in a dark room or without light. This research used a 2 x 2 x 3 factorial Completely Randomized Design (RAL) with 2 factors, namely; The first factor is the seed factor which consists of two levels, namely corn seeds (J), and sorghum seeds (S), and the second factor is harvest age (HST) consisting of 2 levels, namely the 4th day (4), and the 4th day. 7 (7), 3 repetitions each. The two types of seeds and different harvest ages (HST), then the interaction between factors for each germination of corn seeds and sorghum seeds showed significantly different results or effects (P<0.05). The results of this study showed that the germination of corn and sorghum seeds harvested at different ages (HST) had different percentages of germination and root length. The best interaction was shown by corn seed treatment at 7 HST.